2009
DOI: 10.1186/1756-9966-28-23
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on acute inflammation and cancer: a new balance between IFN-γ and TGF-β in melanoma

Abstract: Recent data have redefined the concept of inflammation as a critical component of tumor progression. However, there has been little development on cases where inflammation on or near a wound and a tumor exist simultaneously. Therefore, this pilot study aims to observe the impact of a wound on a tumor, to build a new mouse tumor model with a manufactured surgical wound representing acute inflammation, and to evaluate the relationship between acute inflammation or wound healing and the process of tumor growth. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…A previous study showed that IFN-γ induced by surgical wounds suppresses tumor growth in a syngeneic mouse tumor model [33]. Similar to our results, the growth suppression effect was lost over time and rapid tumor regrowth occurred.…”
Section: Discussionsupporting
confidence: 80%
“…A previous study showed that IFN-γ induced by surgical wounds suppresses tumor growth in a syngeneic mouse tumor model [33]. Similar to our results, the growth suppression effect was lost over time and rapid tumor regrowth occurred.…”
Section: Discussionsupporting
confidence: 80%
“…In fact, the downregulation of TGFβ, which can antagonize IFNγ effects, suggests that the NO-np might modulate the impairment of Ab to disseminate within immune cells. 34 Furthermore, downregulation of the pro-inflammatory cytokine, IL-1β by the NO-np are consistent with the fact that this cytokine can be expressed in late-stage of wound healing and the wounds in our experiments were excised in the early to middle stages of this coordinated process. 35 Incidentally, high levels of IL-1β promote Ab replication within phagocytic cells.…”
Section: 13supporting
confidence: 88%
“…IFN-γ does inhibit human A172 glioma cell transmigration [192]; A172 cells do express gBK (Ge, Hoa and Jadus, unpublished results). B16 melanoma [193] and thyroid cancer cells, likewise are inhibited by IFN-γ in in vitro invasion assays, too [194]. …”
Section: Cancer Immunotherapymentioning
confidence: 99%